Yield and root development of 'Conilon' coffee plants propagated by cuttings and seeds - Partelli, Fábio Luiz; Vieira, Henrique Duarte; Santiago, Anderson Ribeiro; Barroso, Deborah Guerra (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the production and root and shoot development of plants of 'Conilon' coffee, grown from seeds and branches, in Vila Valério, ES, Brazil. The experiment was performed in randomized complete block design, with two treatments (seedlings originated from seeds and branches), and 12 replicates with five plants per plot. Shoot growth evaluation was performed seven months after planting. Six pruning of the orthotropic branches and five yields were evaluated. The evaluation of the root system was done 52 months after planting in four depths (0–10, 10–20, 20–40 and 40–60 cm). Diameter, length and superficial area of roots were quantified. Plants grown from cuttings produced more plagiotropic branches, during the first seven months, and less orthotropic branches throughout the experimental period. There were no differences either in length or superficial area of roots from plants propagated by seeds or cuttings. There was a greater concentration of fine roots in the superficial layers of the soil. The productivity of plants grown from cuttings is higher than that observed in plants grown from seeds.